The Influence of Tomato Juice on Blood Pressure in Menopause Women With Hypertension in Posyandu Kantil - Ria Muji Rahayu (State Islamic University of Sunan Ampel, 2017)
Tomato (Lycopersicum commune) contains potassium and lycopene which has the effect blood pressure. The study aims to understand the effect of tomato juice in menopause women with hypertension. This was a pre experimental research. The population was menopausal women and hypertension case amount 11 persons, using total sampling. The research instrument was observational paper dan sphigmanometer. The research result was analyzed by normality test of Shapiro-Wilk test. Statistical test with Wilcoxon test. The research result shown there is no difference mean value between blood pressure before and after treated by tomato juice. They are 6,00 mmHg (systole) and 1,82 mmHg (diastole). Data analyzed by It is 0,05. obtains p value systole 0,072 and diastole 0,334 where p value < ÃŽÂ±, this H0 is accepted and H1 is rejected. The analysis result shown there is no difference between blood pressure before and after treated by tomato juice at Posyandu Kantil sub-district of Mojoroto, Kediri. Based on the research result revealed there are still many shortcomings that research do so very influential on the final result, and is expected to be study in the future.